A mixture of Nordic berries improves cognitive function, metabolic function and alters the gut microbiota in C57Bl/6J male mice - Huang, Fang; Marungruang, Nittaya; Martinsson, Isak; Camprubí Ferrer, Lluís; Nguyen, Thao Duy; Gondo, Thamani Freedom; Karlsson, Eva Nordberg; Deierborg, Tomas; Öste, Rickard; Heyman-Lindén, Lovisa (Frontiers in Nutrition, 2023)
Our diets greatly influence our health. Multiple lines of research highlight the beneficial properties of eating berries and fruits. In this study, a berry mixture of Nordic berries previously identified as having the potential to improve memory was supplemented to young C57Bl/6J male mice to investigate effects on cognition function, metabolic health, markers of neuroinflammation, and gut microbiota composition. C57Bl/6J male mice at the age of 8 weeks were given standard chow, a high-fat diet (HF, 60%E fat), or a high-fat diet supplemented with freeze-dried powder (20% dwb) of a mixture of Nordic berries and red grape juice (HF+Berry) for 18 weeks (n = 12 animals/diet group). The results show that supplementation with the berry mixture may have beneficial effects on spatial memory, as seen by enhanced performance in the T–maze and Barnes maze compared to the mice receiving the high-fat diet without berries. Additionally, berry intake may aid in counteracting high-fat diet induced weight gain and could influence neuroinflammatory status as suggested by the increased levels of the inflammation modifying IL-10 cytokine in hippocampal extracts from berry supplemented mice. Furthermore, the 4.5-month feeding with diet containing berries resulted in significant changes in cecal microbiota composition. Analysis of cecal bacterial 16S rRNA revealed that the chow group had significantly higher microbial diversity, as measured by the Shannon diversity index and total operational taxonomic unit richness, than the HF group. The HF diet supplemented with berries resulted in a strong trend of higher total OTU richness and significantly increased the relative abundance of Akkermansia muciniphila, which has been linked to protective effects on cognitive decline. In conclusion, the results of this study suggest that intake of a Nordic berry mixture is a valuable strategy for maintaining and improving cognitive function, to be further evaluated in clinical trials.